2022
DOI: 10.1007/s00520-022-06892-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-management by older people living with cancer and multi-morbidity: a qualitative study

Abstract: Purpose Over half of individuals diagnosed with cancer are aged over 70 years, and more than 75% of those with cancer report at least one other medical condition. Having multiple conditions alongside cancer in old age may lower functional status, greater likelihood of treatment complications and less favourable prognoses. This qualitative study explored how older people with long-term chronic conditions manage their health and meet their health-related goals after they have completed treatment for cancer. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In a study of people with cancer and dementia, Griffiths et al (2021) noted that 'Patients with dementia did not always feel a sense of agency to challenge staff or request changes, perceiving this as immoveable or "the appointment we'd been given"'. When interviewing people with chronic conditions as well as cancer, Corbett et al (2022) found that individuals who normally displayed a sense of active agency in managing their health needs, reported ceding control to healthcare professionals when it came to undergoing treatment for cancer. It can be difficult for individuals to exercise agency within a highly structured system upon which they are reliant.…”
Section: Enhancing Agencymentioning
confidence: 99%
“…In a study of people with cancer and dementia, Griffiths et al (2021) noted that 'Patients with dementia did not always feel a sense of agency to challenge staff or request changes, perceiving this as immoveable or "the appointment we'd been given"'. When interviewing people with chronic conditions as well as cancer, Corbett et al (2022) found that individuals who normally displayed a sense of active agency in managing their health needs, reported ceding control to healthcare professionals when it came to undergoing treatment for cancer. It can be difficult for individuals to exercise agency within a highly structured system upon which they are reliant.…”
Section: Enhancing Agencymentioning
confidence: 99%
“…Individuals with multimorbidities' life circumstances change with ongoing personal and structural issues resulting in continuing vulnerabilities. The individuals describe financial issues, low income, rural living conditions, unemployment, transportation issues, poor housing conditions, and physical disabilities affecting their self-management of multimorbidities [25][26][27][28][29][30][31][32][33][34][35]. These circumstances made them vulnerable to poor and inadequate self-management.…”
Section: Analytical Theme One: Contextualized Personal and Structural...mentioning
confidence: 99%
“…Low income [25,26,28,42] Living circumstances and vulnerabilities Contextualized personal and structural vulnerabilities impact access to care and navigation of health care delivery systems Unemployment [25][26][27]33] Financial constraints [25-27, 29-34, 42-45] Limited Transportation [25-27, 30, 32, 34, 35, 38, 43-45] Costly transportation [25,27,35,38] Congested homes many people in a single room or a house [26,42] Out of pocket cost for medications [25,29,30,32,34] Poor housing [26,27,38,42] Rural living [26,32,37,38,42] Living alone [29,38,42] Limited education/literacy level [25,36] Disability prevented from traveling to health care facilities [30,43] Non-sustainable private health insurances [31,32] Scarce health care resources Cutbacks and reductions in insurances [32] Inadequate medical facilities in the community [25,27,28,30,…”
Section: Codes Descriptive Themes Analytical Themementioning
confidence: 99%
“…Over the last decade, there has been an international drive towards promoting and supporting self‐management with people living with cancer 18–21 . Self‐management means managing the physical, psychological, social and practical consequences of cancer and its treatment as well as understanding how and when to seek support, recognising signs of disease progression and making lifestyle changes to promote health and wellbeing 22 .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Over the last decade, there has been an international drive towards promoting and supporting self-management with people living with cancer. [18][19][20][21] Self-management means managing the physical, psychological, social and practical consequences of cancer and its treatment as well as understanding how and when to seek support, recognising signs of disease progression and making lifestyle changes to promote health and wellbeing. 22 Prominent psycho-social oncology researchers Foster and Fenlon consider engagement with self-management crucial when it comes to the recovery of health and wellbeing following cancer treatment.…”
Section: Introductionmentioning
confidence: 99%